Fourth Periodic Monitoring Report on the Status of Implementation Plans in Response to Board-Endorsed IEO Recommendations : Assessment by the Evaluation Committee to the Executive Board. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Executive Board agreed in January 2008 to refer future Periodic Monitoring Reports (PMRs) to the Evaluation Committee (EVC) for initial consideration and review before reporting to the full Board. It was expected that, although a Board discussion could not be ruled out, in most cases the EVC discussion would replace a Board discussion. This procedure, which was intended to make better use of Board Committees and more efficient use of Board time, was applied to the consideration of the previous PMRs and has been followed for the Fourth PMR.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Board Discussion; Board; IEO Recommendation; IEO; PP